The Value of a Standardized Knee Functional Assessment in Predicting the Outcomes of Total Knee Arthroplasty - Ferreira, Aline Miranda; Salim, Rodrigo; Fogagnolo, Fabricio; de Oliveira, Luciano Fonseca Lemos; Riberto, Marcelo; Kfuri, Mauricio (The Journal of Knee Surgery, 2021)
Questionnaires and physical tests are tools to determine the ability of an individual to perform tasks of the daily living. In our institution, a standardized knee performance evaluation including patient-reported outcome measures (PROMs) and physical performance tests has been applied to all patients undergoing total knee arthroplasty (TKA). Our goal was to identify which preoperative tools influence the outcomes of a TKA and if physical performance tests can be of value if used along with PROMs in predicting functional outcomes. Classification and regression tree was used to analyze which preoperative factors influence function after TKA. Western Ontario and McMaster Universities Arthritis Index (WOMAC) function (WOMAC-F), 6-minute walk test (6MWT), and timed up and go (TUG) test at the 12th postoperative month were the dependent variables. Age, body mass index, preoperative WOMAC function and pain score, muscle strength, 6MWT, and TUG test score were used as preoperative predictors of dependent variables. TUG ≤19.3 seconds and age <62 years were preoperative predictors of better scores in the WOMAC-F (5.5). Strength of extensor muscles of the nonoperated knee ≥99.43 N·m/kg and 6MWT> 328 m were preoperative predictors of a better postoperative 6MWT (499 m). TUG <12.3 seconds and 6MWT ≥421 m were preoperative predictors of better postoperative TUG (7.3 seconds). Preoperative performance in physical tests had an influence on postoperative outcome scores than PROMs after TKA. Less age, good muscular strength, greater capacity of walking, and smaller TUG times were associated with better outcomes.
Keywords: knee osteoarthritis; total knee arthroplasty; performance; function; assessment